2020
DOI: 10.33003/fjs-2020-0403-361
|View full text |Cite
|
Sign up to set email alerts
|

Household’s Responses to the Roles of Trees as Wind Breaker in Dutse Local Government Area of Jigawa State, Nigeria

Abstract: Wind is a natural process through which air moves in mass from high pressure areas to low pressure areas. There is no doubt when not obstructed can damage several natural features and human-made structures beyond repairs. However, in an open landscape trees provide the most effective protection compared to other biological wind control measures. This study investigated household’s responses to the roles of trees as wind breaker in Dutse Local Government Area of Jigawa State, Nigeria. The data were collected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The prominent religion in the study area was Muslim (91.43%). This supported the observations of Ilu et al [22] and Lawal et al [29] who reported the higher percentage of married respondents, male and muslim and non formal education in the same study area.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prominent religion in the study area was Muslim (91.43%). This supported the observations of Ilu et al [22] and Lawal et al [29] who reported the higher percentage of married respondents, male and muslim and non formal education in the same study area.…”
Section: Discussionsupporting
confidence: 92%
“…Dutse is located on the Latitude of 11.00 [22]; Salami and Lawal [23]. Some of the settlements in the area include; Fagoji, Kaci, Limawa, Gidadubi, Danmasara, Madobi, Zai, Kude, Takur, And Jigawar Tsada, which are made up of Hausa, Fulani, and Mangawa.…”
Section: Methodology 21 Description Of the Study Areamentioning
confidence: 99%
“…Acacia senegal commonly called Gum Arabic belongs to the family Fabaceae (Jibo et al, 2018a). It nurtures comfortably on two different kinds of soils which are sandy and loamyclay soil, it endures pH of 5 -8 (Ampitan et al, 2022;Ilu et al, 2020;Jibo et al, 2018a). Gum Arabic actively produced good vigour in a drained soil with rainfall which ranges between 200 to 800mm annually.…”
Section: Introductionmentioning
confidence: 99%
“…Several million households worldwide depend heavily on NTFPs for subsistence or income. Research showed that rural people in the Northern part of Nigeria depend largely on fuel-wood and charcoal as a dominant biomass energy sources and also aware of mitigating methods (Orifah et al, 2018;Ilu et al, 2020). Women from poor households generally rely on them most for household use and income.…”
Section: Introductionmentioning
confidence: 99%